Optical resin, and optical film, polarizing plate, surface plate, image display panel, image display device, and optical molded article using optical resin
By controlling the peak-area ratio of the 13C-NMR spectrum in the optical resin and using alternating copolymers of maleimide-based monomers and styrene-based monomers, the problem of birefringence of optical polymer materials under molding and loading is solved, effectively suppressing stress birefringence and improving optical performance are achieved.
Patent Information
- Application Number
- CN202510234213.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-26
- Filing Date
- 2023-04-25
- Publication Date
- 2025-05-02
AI Technical Summary
Existing optical polymer materials are prone to birefringence during molding, and birefringence problems will also occur when loading is applied, which is difficult to effectively suppress.
A specific optical resin is used, and the ratio of the peak area ratio of the range of 141 ppm to 147 ppm in the 13C-NMR spectrum to the peak area ratio of 135 ppm to 141 ppm is 0.55 or less. Birefringence caused by stress is suppressed by alternating copolymers of maleimide-based monomers and styrene-based monomers.
It effectively suppresses birefringence caused by stress, improves the abrasion resistance and heat resistance of the optical resin, and reduces haze. It is suitable for optical films, polarizers, surface panels, image display panels and optical molded products.
Smart Images

Figure CN119912639A_ABST
Abstract
Description
[0001] This application is a divisional application. The application number of the original application is 202380045229.4, the application date is April 25, 2023, and the name of the invention is "Optical resin, and optical film, polarizer, surface plate, image display panel, image display device and optical molded product using the above optical resin." Technical Field
[0002] The present disclosure relates to an optical resin, and an optical film, a polarizing plate, a surface plate, an image display panel, an image display device, and an optical molded product using the optical resin. Background Art
[0003] Image display devices such as liquid crystal display devices and organic EL display devices are used as display devices for various devices. For example, these display devices are used for display devices of personal computers; television receivers; vehicle instrument panels; vehicle navigation devices; portable information terminal devices such as smartphones; digital signage; etc.
[0004] In these image display devices, in order to improve visibility or suppress surface damage, an optical film is sometimes used. For the optical film used in the image display device, in order to improve visibility, it is desired to suppress birefringence. In addition, for optical lenses such as pickup lenses, augmented reality lenses (AR lenses), virtual reality lenses (VR lenses), mixed reality lenses (MR lenses), LiDAR lenses, camera lenses, and components of the backlight source of a liquid crystal display device, it is also desired to suppress birefringence. Therefore, for optical resins as materials for components such as optical films, optical lenses, and backlight sources, low birefringence is also required.
[0005] In order to suppress the birefringence of the resin, it is preferable that the intrinsic birefringence and the photoelastic coefficient are small. As a resin for suppressing the birefringence, for example, an optical polymer material of Patent Document 1 is proposed.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2020-126229 Summary of the invention
[0009] Problems to be solved by the invention
[0010] However, parts using the optical polymer material of Patent Document 1 may generate birefringence. For example, a molded product formed by injection molding the optical polymer material of Patent Document 1 may generate birefringence due to stress remaining inside the molded product. In addition, an optical film using the optical polymer material of Patent Document 1 may generate birefringence when a load is applied.
[0011] The present invention provides an optical resin that can suppress birefringence caused by stress such as internal stress and external stress. In addition, the present invention provides an optical film, a polarizing plate, a surface plate, an image display panel, an image display device, and an optical molded product using the optical resin.
[0012] Means for solving problems
[0013] The present disclosure provides the following [1] to [7].
[0014] [1] An optical resin, wherein 13 In the C-NMR spectrum, when the range of chemical shift from 141 ppm to 147 ppm is defined as the first range, and the range of chemical shift from 135 ppm to 141 ppm is defined as the second range, the ratio of the peak area of the peak in the first range to the peak area of the peak in the second range is less than 0.55.
[0015] [2] An optical film comprising the optical resin described in [1].
[0016] [3] A polarizing plate comprising: a polarizing element; a first transparent protective plate disposed on one side of the polarizing element; and a second transparent protective plate disposed on the other side of the polarizing element, wherein:
[0017] At least one of the first transparent protective plate and the second transparent protective plate includes the optical film described in [2].
[0018] [4] A surface plate for an image display device, comprising a resin plate or a glass plate to which a protective film is laminated, wherein the protective film comprises the optical film according to [2].
[0019] [5] An image display panel comprising the optical film described in [2] on a display element.
[0020] [6] An image display device comprising the image display panel described in [5].
[0021] [7] An optical molded article comprising the optical resin described in [1].
[0022] Effects of the Invention
[0023] The optical resin disclosed herein, and an optical film, a polarizing plate, a surface plate, an image display panel, an image display device, and an optical molded product using the optical resin can suppress the occurrence of birefringence due to stress. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a top view for explaining a sample for measuring the photoelastic coefficient. DETAILED DESCRIPTION
[0025] Hereinafter, the optical resin of the present disclosure, and an optical film, a polarizing plate, a surface plate, an image display panel, an image display device, and an optical molded product using the optical resin will be described.
[0026] [Optical resin]
[0027] In the optical resin disclosed in the present invention, 13 In the C-NMR spectrum, when the range of chemical shift from 141 ppm to 147 ppm is defined as the first range, and the range of chemical shift from 135 ppm to 141 ppm is defined as the second range, the ratio of the peak area of the peak in the first range to the peak area of the peak in the second range is less than 0.55.
[0028] about 13 In the C-NMR spectrum, the peak in the first range with a chemical shift of 141 ppm to 147 ppm is a peak derived from the benzene ring of the styrene-based monomers, which is generated when the styrene-based monomers are polymerized with each other. 13 In the C-NMR spectrum, the peak in the second range with a chemical shift of 135 ppm to 141 ppm is a peak derived from the benzene ring of the styrene monomer, which is generated when the maleimide monomer and the styrene monomer are alternately copolymerized.
[0029] Therefore, "the ratio of the peak area of the peak in the first range to the peak area of the peak in the second range" represents "the ratio of the homopolymer of the styrene-based monomer in the optical resin to the alternating copolymer of the maleimide-based monomer and the styrene-based monomer in the optical resin".
[0030] That is, the ratio of the peak area of the peak in the first range to the peak area of the peak in the second range being 0.55 or less means that the proportion of the homopolymer of the styrene monomer to the alternating copolymer of the maleimide monomer and the styrene monomer in the optical resin is small.
[0031] In this specification, "the ratio of the peak area of the peak in the first range to the peak area of the peak in the second range" may be referred to as "peak area ratio".
[0032] The optical resin disclosed herein has at least a peak area of a peak in the second range. The optical resin disclosed herein may or may not have a peak area of a peak in the first range. Specific examples of peak area ratios are shown in (1) to (4) below. (1) and (2) below are optical resins corresponding to the examples, and (3) and (4) below are optical resins corresponding to the comparative examples.
[0033] (1) In the present specification, for an optical resin in which the peak area of the peak in the second range is 100 and the peak area of the peak in the first range is 0, the peak area ratio is set to 0.
[0034] (2) In the present specification, for an optical resin in which the peak area of the peak in the second range is 100 and the peak area of the peak in the first range is 50, the peak area ratio is set to 0.50.
[0035] (3) In the present specification, for an optical resin in which the peak area of the peak in the second range is 0 and the peak area of the peak in the first range is 100, the peak area ratio is infinite (represented as "∞" in comparative examples).
[0036] (4) In the present specification, for an optical resin having a peak area of 0 in the second range and a peak area of 0 in the first range, the peak area ratio cannot be determined (represented as "-" in comparative examples).
[0037] The alternating copolymer of the maleimide monomer and the styrene monomer can suppress the occurrence of birefringence due to stress by mutually suppressing the stereo conformation which is the motion of the molecules.
[0038] However, even if the optical resin includes an alternating copolymer of a maleimide-based monomer and a styrene-based monomer, if the ratio of the homopolymer of the styrene-based monomer increases and the peak area ratio exceeds 0.55, birefringence due to stress cannot be suppressed.
[0039] In addition, the homopolymer of maleimide monomer and the homopolymer of styrene monomer each have a positive photoelastic birefringence. Therefore, the resin formed by blending the homopolymer of styrene monomer and the homopolymer of maleimide monomer cannot suppress the birefringence caused by stress. The resin formed by blending the homopolymer of styrene monomer and the homopolymer of maleimide monomer cannot reduce the haze and is therefore not suitable for optical applications.
[0040] The peak area ratio of the optical resin disclosed in the present invention is 0.55 or less, so that birefringence due to stress can be suppressed. The peak area ratio of the optical resin is preferably 0.40 or less, more preferably 0.25 or less, and more preferably 0.15 or less. The peak area ratio of the optical resin may also be 0. The peak area ratio of the optical resin being 0 means that the optical resin contains an alternating copolymer of a maleimide monomer and a styrene monomer, but does not contain a homopolymer of a styrene monomer.
[0041] By setting the peak area ratio of the optical resin to 0.55 or less, the haze of the optical resin can be further easily reduced. By setting the peak area ratio of the optical resin to 0.55 or less, the scratch resistance such as pencil hardness and steel wool resistance can be further easily improved.
[0042] As the situation where stress is applied to the optical resin or internal stress remains in the optical resin, for example, the following (1) to (3) can be mentioned.
[0043] (1) Molded products made of optical resins are prone to residual stress in the resin. In particular, during injection molding and extrusion molding, the optical resin is rapidly cooled from a high temperature state, so internal stress is likely to remain.
[0044] (2) When heat is applied to an article made of an optical resin, stress is easily applied to the resin when the article expands due to heat.
[0045] (3) When an article made of an optical resin is assembled into a device such as a liquid crystal display device by fixing or bonding, stress is likely to be applied to the resin.
[0046] In this manual, 13 The C-NMR spectrum can be measured, for example, by the method described in Examples.
[0047] The optical resin preferably includes an alternating copolymer of a maleimide-based monomer and a styrene-based monomer.
[0048] <Maleimide Monomer>
[0049] Examples of the maleimide monomer include maleimide (unsubstituted maleimide), N-substituted maleimide, and maleimide derivatives other than N-substituted maleimide.
[0050] N-substituted maleimide is obtained by replacing the hydrogen atom bonded to the nitrogen atom of maleimide with a substituent. As the substituent, a substituent having 1 to 6 carbon atoms is preferred, a hydrocarbon group having 1 to 6 carbon atoms is more preferred, and an alkyl group having 1 to 6 carbon atoms is further preferred.
[0051] The above-mentioned hydrocarbon group and the above-mentioned alkyl group may have a substituent.
[0052] The above-mentioned alkyl group may be linear or branched.
[0053] If a cycloalkyl group is included as the substituent, the optical resin is easily broken during molding. Therefore, as the substituent, an alkyl group having 1 to 6 carbon atoms is preferred.
[0054] The maleimide-based monomer can be represented by, for example, the following general formula (I).
[0055] [Chemistry 1]
[0056]
[0057] In the formula (I), “R” includes hydrogen; methyl, ethyl, propyl, isopropyl, butyl, 1-methylpropyl, 2-methylpropyl, pentyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 2,2-dimethylpropyl, 1-ethylpropyl, 2-ethylpropyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, hexyl, 1-methylpentyl, 2-methylpentyl, 3-methylpentyl, 4-methylpentyl, 1-ethylbutyl, 2-ethylbutyl, 1,1-dimethylbutyl, 1,2-dimethylbutyl, 1,3-dimethylbutyl, 2,2-dimethylbutyl, 2,3-dimethylbutyl, 1,1 Alkyl groups which may have substituents include alkyl groups such as alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group, alkyl group
[0058] In formula (I), "R" is preferably an alkyl group having 1 to 6 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms and having no substituent, and further preferably an alkyl group having 3 to 5 carbon atoms and having no substituent. The reason why the alkyl group having no substituent is preferred is that the halogen as a substituent has a high burden on the environment, and the hydroxyl group as a substituent tends to increase the viscosity due to the absorption of water, etc., and the workability of molding is reduced. The reason why the alkyl group having 1 to 6 carbon atoms is preferred is that "the more the number of carbon atoms increases, the lower the glass transition temperature of the optical resin, and the easier it is to lower the molding temperature"; and "by setting the number of carbon atoms to 6 or less, the viscosity increase during molding can be suppressed". However, in the alkyl group having 1 to 6 carbon atoms, the tert-butyl group is easily decomposed by heat, so it is not preferred.
[0059] As can be seen from the above, in formula (I), "R" is preferably propyl, isopropyl, butyl, isobutyl, sec-butyl, pentyl, isopentyl, sec-pentyl, or tert-pentyl.
[0060] In formula (I), "X 1 ” and “X 2 "X" includes hydrogen, fluorine, chlorine, bromine, iodine, methyl and the like. 1 ” and “X 2 " can be the same or different. In formula (I), "X 1 ” and “X 2 " is preferably hydrogen. "X 1 ” and “X 2" In the case of a halogen, the burden on the environment becomes high, which is not preferred.
[0061] The maleimide monomer preferably contains one or more selected from maleimide and N-substituted maleimide substituted with a hydrocarbon group having 1 to 6 carbon atoms.
[0062] <Styrene Monomer>
[0063] Examples of the styrene-based monomers include styrene and styrene derivatives.
[0064] The styrene-based monomer can be represented by, for example, the following general formula (II).
[0065] [Chemistry 2]
[0066]
[0067] In formula (II), "X 1 ”, “X 2 ” and “X 3 "X" includes hydrogen, fluorine, chlorine, bromine, iodine, hydroxyl and methyl. 1 ”, “X 2 ” and “X 3 " can be the same or different.
[0068] Halogen as a substituent has a high burden on the environment, and hydroxyl as a substituent tends to increase the viscosity due to water absorption, etc., which reduces the workability of molding. 1 ”, “X 2 ” and “X 3 " is preferably hydrogen or methyl, more preferably hydrogen.
[0069] In formula (II), "Y 1 ”~“Y 5 " " may include hydrogen, fluorine, chlorine, bromine, iodine, hydroxyl, methyl, hydroxymethyl, ethyl, propyl, isopropyl, butyl, tert-butyl, pentyl and hexyl. "Y 1 ”~“Y 5 " can be the same or different.
[0070] Halogen as a substituent has a high burden on the environment, and hydroxyl as a substituent tends to increase viscosity due to water absorption, etc., which reduces the workability of molding. 1 ”~“Y 5 When " is an alkyl group with 2 or more carbon atoms, the fluidity of the optical resin when it is melted is reduced. Therefore, in formula (II), "Y 1 ”~“Y 5 " is preferably hydrogen or methyl, more preferably hydrogen.
[0071] As the styrene monomer, it is preferred to include at least one selected from styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene and p-methylstyrene. Among the styrene monomers, styrene is preferred because it is easy to adjust the glass transition temperature, thus suppressing embrittlement and easily lowering the temperature during molding.
[0072] Ingredients from biomass
[0073] At least one monomer selected from the maleimide monomer and the styrene monomer preferably contains a component derived from biomass. By using a monomer containing a component derived from biomass, the biomass degree of the optical resin can be increased. In addition, the preferred embodiment of the optical resin disclosed herein is useful in that the birefringence caused by stress can be suppressed despite the high biomass degree of the optical resin.
[0074] As the monomer containing a biomass-derived component, first, there can be mentioned a maleimide-based monomer obtained by reacting biomass-derived maleic anhydride with a primary amine.
[0075] Maleic anhydride from biomass can be obtained, for example, through "Step 1 of obtaining a mixture of fumaric acid and maleic acid from furfural" and "Step 2 of obtaining maleic anhydride by dehydrating the maleic acid obtained in step 1". Furfural can be obtained, for example, from agricultural by-products such as corn cobs, rice husks, bagasse, cotton husks, oat husks, almond husks, and olive press cakes. The method of obtaining furfural from agricultural by-products is reported in "Development of bio-based materials using furfural as raw material, Journal of the Japanese Society of Adhesion Research Vol. 53 No. 8 (2017)" by Tachibana Kumano, Hayashi Chisato, and Kasuya Kenichi.
[0076] Maleimide monomers obtained by reacting biomass-derived maleic anhydride with a primary amine are preferred because optical properties such as the refractive index can be easily adjusted by changing the type of the primary amine.
[0077] Examples of the primary amine include methylamine, ethylamine, propylamine, isopropylamine, butylamine, isobutylamine, sec-butylamine, pentylamine, isopentylamine, sec-pentylamine, and tert-pentylamine. Among these, propylamine, isopropylamine, butylamine, isobutylamine, sec-butylamine, pentylamine, isopentylamine, sec-pentylamine, and tert-pentylamine are preferred.
[0078] As a monomer containing a component derived from biomass, secondly, a styrene monomer obtained by reacting ethylene derived from biomass with benzene derived from biomass can be cited. α-methylstyrene, o-methylstyrene, m-methylstyrene, and p-methylstyrene tend to increase carbon dioxide emissions due to the increase in the number of steps required to produce the monomers. Therefore, the styrene monomer is preferably styrene itself.
[0079] Ethylene and benzene from biomass can be obtained, for example, through "step 1 of decomposing lignocellulose into a water-soluble compound group having about 2 to 6 carbon atoms" and "step 2 of converting the water-soluble compound group obtained in step 1 into olefin hydrocarbons such as ethylene, propylene and butene, and aromatic hydrocarbons such as benzene, toluene and xylene using a solid acid catalyst". These steps are reported on the homepage of Nippon Shokubai Co., Ltd. (https: / / www.shokubai.co.jp / ja / news / news0275.html).
[0080] As an example of an alternating copolymer of a maleimide monomer and a styrene monomer, the structural formula of an alternating copolymer of maleimide and styrene is shown below. Since the polymerization reaction of maleimide monomers and styrene monomers has a very small monomer reactivity ratio r1 and r2, an alternating copolymer is easily formed.
[0081] [Chemistry 3]
[0082]
[0083] The optical resin disclosed in the present invention can be obtained by, for example, polymerizing a maleimide-based monomer and a styrene-based monomer.
[0084] As described above, the polymerization reaction of maleimide monomers and styrene monomers is easy to form an alternating copolymer because the monomer reactivity ratios r1 and r2 are extremely small. Therefore, in the binary system, in the optical resin, the molar ratio of maleimide monomers to styrene monomers is easy to be about 50:50. In the optical resin, when the proportion of maleimide monomers is increased, as a raw material monomer, it is sufficient to increase the proportion of maleimide monomers relative to styrene monomers. In addition, in the optical resin, when the proportion of styrene monomers is increased, as a raw material monomer, it is sufficient to increase the proportion of styrene monomers relative to maleimide monomers.
[0085] In the binary system, in the optical resin, the molar ratio of the maleimide monomer to the styrene monomer is preferably 41:59 to 75:25, more preferably 45:55 to 70:30, more preferably 50:50 to 65:35, more preferably 50:50 to 60:40, and more preferably 50:50 to 55:45. By making the molar ratio of the maleimide monomer to the styrene monomer within the above range, it is easy to make the peak area ratio within the above range, and the haze can be easily reduced. The homopolymer of the styrene monomer and the alternating copolymer of the maleimide monomer and the styrene monomer have different refractive indices, so by increasing the proportion of the maleimide monomer as described above, the haze can be easily reduced. In addition, as described above, by not excessively increasing the proportion of the maleimide monomer, it is possible to prevent the article containing the optical resin from becoming brittle and breaking.
[0086] The molar ratio of maleimide monomer to styrene monomer in the optical resin can be determined by 13 It was calculated by measuring the C-NMR spectrum.
[0087] The optical resin of the present disclosure may use other monomers other than maleimide monomers and styrene monomers as polymerizable monomer components within the scope that does not hinder the effects of the present disclosure. In other words, the optical resin of the present disclosure may contain a multi-component copolymer of maleimide monomers, styrene monomers and other monomers within the scope that does not hinder the effects of the present disclosure. The multi-component copolymer may be a terpolymer in which the other monomer is one kind, or may be a tetrapolymer or more in which the other monomer is two or more kinds.
[0088] Examples of other monomers include monomers having ethylenically unsaturated bond groups such as (meth)acryloyl, vinyl, and allyl groups. Specific examples of other monomers include ethylene, methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, and isobutylene.
[0089] In the multi-component copolymer, the molar ratio of "maleimide monomer" to "total of styrene monomer and other monomers" is preferably 41:59 to 75:25, more preferably 45:55 to 70:30, more preferably 50:50 to 65:35, more preferably 50:50 to 60:40, more preferably 50:50 to 55:45.
[0090] If the optical resin contains a resin other than an alternating copolymer of a maleimide monomer and a styrene monomer, the haze tends to be high. On the other hand, a multi-component copolymer is useful in that the haze is unlikely to be increased.
[0091] The optical resin of the present disclosure may contain resins other than the alternating copolymers of maleimide monomers and styrene monomers within the range that does not hinder the effects of the present disclosure. As resins other than the alternating copolymers of maleimide monomers and styrene monomers, homopolymers of maleimide monomers, homopolymers of styrene monomers, terpolymers of maleimide monomers, styrene monomers and other monomers, etc. can be cited.
[0092] If the optical resin contains a resin other than the alternating copolymer of maleimide monomers and styrene monomers, the haze tends to increase. Therefore, in order to easily suppress the generation of birefringence due to stress, the mass ratio of the alternating copolymer of maleimide monomers and styrene monomers to the total amount of the optical resin disclosed in the present invention is preferably 40 mass % or more, more preferably 50 mass % or more, further preferably 60 mass % or more, further preferably 80 mass % or more, further preferably 90 mass % or more.
[0093] The lower limit of the weight average molecular weight of the alternating copolymer of maleimide monomer and styrene monomer is preferably 30,000 or more, more preferably 80,000 or more, and further preferably 100,000 or more, and the upper limit is preferably 3,000,000 or less, more preferably 1,500,000 or less, further preferably 800,000 or less, and further preferably 600,000 or less. The weight average molecular weight of the multi-component copolymer of maleimide monomer, styrene monomer and other monomers is also preferably within the above range.
[0094] By making the weight average molecular weight greater than 30,000, it is possible to prevent the articles containing the optical resin from becoming brittle and breaking. By making the weight average molecular weight less than 3,000,000, it is easy to dissolve the optical resin in a solvent, and it is easy to prevent the melt viscosity of the optical resin from becoming too high, so that the processability of the articles containing the optical resin can be easily improved. In order to reduce the melt viscosity, the weight average molecular weight is preferably less than 600,000.
[0095] In this specification, the weight average molecular weight is an average molecular weight measured by GPC analysis and converted into standard polystyrene.
[0096] <Physical properties>
[0097] In order to suppress the occurrence of birefringence due to stress, the absolute value of the photoelastic coefficient of the optical resin disclosed in the present invention is preferably 6.0×10 -12 / Pa or less, more preferably 4.0×10 -12 / Pa or less, more preferably 3.0×10 -12 / Pa or less, more preferably 2.0×10 -12 / Pa or less, more preferably 1.5×10 -12 / Pa or less.
[0098] In order to improve heat resistance, the glass transition temperature of the optical resin disclosed in the present invention is preferably 100° C. or higher, more preferably 120° C. or higher. CPUs used in image display devices such as personal computers and smartphones are mostly designed to have a maximum temperature of around 100° C. Therefore, by setting the glass transition temperature to 100° C. or higher, the optical resin disclosed in the present invention can be easily applied to image display devices.
[0099] The glass transition temperature of the optical resin disclosed in the present invention is preferably 190°C or less, more preferably 180°C or less, and further preferably 175°C or less. By setting the glass transition temperature to 190°C or less, the temperature during molding can be lowered, so that thermal decomposition of the optical resin can be easily suppressed. In addition, if the glass transition temperature of the optical resin becomes high, the bending resistance is easily reduced, so cracks are easily generated when the optical film is rolled into a roll or the molded product is subjected to curved surface processing. In order to suppress cracks, the glass transition temperature is preferably 175°C or less, and more preferably 160°C or less.
[0100] The glass transition temperature of the optical resin can be easily increased by, for example, "increasing the ratio of maleimide monomers", "making the substituent of N-substituted maleimide an alkyl group having a branched chain", or "reducing the number of carbon atoms of the substituent of N-substituted maleimide".
[0101] In this specification, the glass transition temperature means a value measured as "midpoint glass transition temperature" in differential scanning calorimetry of JIS K7121:1987.
[0102] The refractive index of the optical resin disclosed in the present invention at a wavelength of 589 nm is preferably 1.48 to 1.57, and more preferably 1.49 to 1.56. By making the refractive index 1.48 to 1.57, when a functional layer is laminated on the optical film disclosed in the present invention, the refractive index difference between the optical film and the functional layer can be easily reduced, so that the reflection at the interface between the optical film and the functional layer can be easily suppressed.
[0103] When an optical resin is used for a lens, it is also preferred that the refractive index is higher than the above range. Specifically, when an optical resin is used for a lens, the refractive index may be 1.48 to 1.80. In the case of an AR lens or a VR lens, the refractive index is preferably 1.55 to 1.65.
[0104] Regarding the refractive index of the optical resin, a film is made from the optical resin, and the refractive index is measured by the method described in the examples using the film. In the case of a molded product formed from an optical resin, the optical resin constituting the molded product is dissolved in a solvent, the dissolved solution is formed into a film by a casting method, and the film formed is used to measure the refractive index by the method described in the examples. However, in the case of a molded product in the shape of a flat plate, the refractive index can also be measured by the method described in the examples in the state of the molded product.
[0105] [Optical film]
[0106] The optical film of the present disclosure includes the optical resin of the present disclosure described above.
[0107] Since the resin component of the optical film of the present disclosure is composed of the optical resin of the present disclosure, the occurrence of birefringence due to stress can be suppressed.
[0108] The optical film of the present disclosure may contain additives as components other than the optical resin of the present disclosure. Examples of the additives include ultraviolet absorbers, light stabilizers, antioxidants, anti-blocking agents, and refractive index adjusters.
[0109] In order to improve the mechanical strength, the thickness of the optical film is preferably 10 μm or more, more preferably 20 μm or more, and further preferably 30 μm or more.
[0110] In order to improve process suitability, the thickness of the optical film is preferably 100 μm or less, more preferably 80 μm or less, and further preferably 60 μm or less.
[0111] In this specification, the thickness of an optical film refers to the average value of the thickness at any 10 locations of the optical film. The thickness at any 10 locations of the optical film can be measured using a general-purpose film thickness meter.
[0112] The optical film can be manufactured by a common film forming method such as a casting method and an inflation method. In order to improve the planarity of the optical film, the temperature during film formation is preferably below the glass transition temperature. On the other hand, if the temperature during film formation is too low, sometimes the solvent remains and the physical properties of the optical film are reduced. Therefore, the temperature during film formation is preferably above 100°C.
[0113] The optical film may also be a film stretched by uniaxial stretching, biaxial stretching, etc. That is, the optical film may be a stretched film. A stretched film is easily shrunk by heat, but the optical film of the present disclosure can suppress the generation of birefringence even if stress caused by shrinkage occurs.
[0114] The haze of the optical film in JIS K7136:2000 is preferably 2.0% or less, more preferably 1.0% or less, more preferably 0.7% or less, and more preferably 0.5% or less.
[0115] The total light transmittance of the optical film according to JIS K7361-1:1997 is preferably 85% or more, more preferably 87% or more, and even more preferably 90% or more.
[0116] <Size, shape, etc.>
[0117] The optical film and the polarizing plate described later may be in the form of a single leaf cut into a specified size, or in the form of a roll in which a long sheet is rolled up. The size of the single leaf is not particularly limited, and the maximum diameter is about 2 inches to 500 inches. The "maximum diameter" refers to the maximum length when any two points of the optical film are connected. For example, when the optical film is rectangular, the diagonal of the rectangle is the maximum diameter. When the optical film is circular, the diameter of the circle is the maximum diameter.
[0118] The width and length of the roll are not particularly limited, and generally, the width is 500 mm to 8000 mm, and the length is 100 m to 10000 m. The optical film in roll form can be cut into a single leaf shape according to the size of the image display device, etc. When cutting, it is preferred to exclude the end of the roll where the physical properties are unstable.
[0119] The shape of a single leaf is not particularly limited, and may be, for example, a polygon such as a triangle, a quadrilateral, or a pentagon, or may be a circle, or may be a random amorphous shape.
[0120] [Polarizing plate]
[0121] The polarizing plate disclosed herein is a polarizing plate comprising a polarizing element, a first transparent protective plate arranged on one side of the polarizing element, and a second transparent protective plate arranged on the other side of the polarizing element, wherein at least one of the first transparent protective plate and the second transparent protective plate contains the optical film disclosed herein.
[0122] <Polarizing Element>
[0123] As polarizing elements, there can be mentioned sheet-type polarizing elements such as polyvinyl alcohol film, polyvinyl formal film, polyvinyl acetal film, ethylene-vinyl acetate copolymer saponified film, etc., which are dyed with iodine or the like and stretched; wire grid polarizing elements composed of a large number of metal wires arranged in parallel; coating polarizing elements coated with lyotropic liquid crystal or dichroic host-guest material; multilayer thin film polarizing elements, etc. These polarizing elements can be reflective polarizing elements having the function of reflecting non-transmitted polarized components.
[0124] In this specification, a "polarizing element" refers to a material having a function of transmitting light in a predetermined vibration direction but not transmitting light in a vibration direction nearly perpendicular to the vibration direction. Not transmitting means absorbing and / or reflecting.
[0125] <Transparent protective plate>
[0126] A first transparent protective plate is disposed on one side of the polarizing element, and a second transparent protective plate is disposed on the other side. At least one of the first transparent protective plate and the second transparent protective plate includes the optical film of the present disclosure.
[0127] When a transparent protective plate that generates birefringence due to stress is used as a transparent protective plate of a polarizing element, light cannot be cut off even if two polarizing plates are arranged in orthogonal Nicols, and light leakage may occur. The polarizing plate disclosed in the present invention can suppress light leakage by including the above-mentioned optical film disclosed in the present invention as at least one of the first transparent protective plate and the second transparent protective plate.
[0128] The polarizing plate of the present disclosure preferably includes both the first transparent protective plate and the second transparent protective plate including the optical film of the present disclosure.
[0129] As the transparent protective plate that does not include the optical film of the present disclosure among the first transparent protective plate and the second transparent protective plate, a general-purpose plastic film, glass, or the like can be used.
[0130] The polarizing element and the transparent protective plate are preferably bonded together via an adhesive. A general-purpose adhesive can be used as the adhesive, and a PVA-based adhesive or an ultraviolet curing adhesive is preferred.
[0131] The first transparent protective plate and / or the second transparent protective plate may be an optical layered body in which a functional layer is layered on the optical film of the present disclosure.
[0132] <Optical layered body>
[0133] The optical layered body has one or more functional layers on the optical film of the present disclosure.
[0134] Functional Layer
[0135] The functional layer may have a single-layer structure or a multi-layer structure. The functional layer may be formed on only one side of the optical film or on both sides.
[0136] Examples of the layers constituting the functional layer include an easy-adhesion layer, a phase difference layer, a hard coat layer, an anti-glare layer, an anti-reflection layer, an antifouling layer, an antistatic layer, a specific wavelength absorption layer, a specific wavelength reflection layer, a decorative layer, and an adhesive layer. The functional layer may have multiple functions in one layer.
[0137] The anti-reflection layer in the functional layer can be a single layer structure and a multilayer structure. As a single layer anti-reflection layer, a single layer of a low refractive index layer can be cited. The multilayer anti-reflection layer can be cited as 2 layers of a high refractive index layer and a low refractive index layer, and can also be cited as a structure of more than 3 layers.
[0138] The configuration of functional layers such as the adhesive layer, the phase difference layer, the hard coat layer, the antiglare layer, the antireflection layer, the antifouling layer, the antistatic layer, and the adhesive layer can be a common configuration.
[0139] As the lamination structure of the optical layered body, for example, the following embodiments B1 to B15 can be cited. In the following B1 to B15, " / " refers to the interface of the layer. In the following lamination structure B1 to B15, an embodiment having an easy-adhesion layer between one or more layers can also be cited.
[0140] B1: Optical film / hard coating
[0141] B2: Optical film / anti-glare layer
[0142] B3: Optical film / hard coating / anti-reflective layer
[0143] B4: Optical film / anti-glare layer / anti-reflection layer
[0144] B5: Optical film / hard coating / antifouling layer
[0145] B6: Optical film / anti-glare layer / anti-fouling layer
[0146] B7: Optical film / phase difference layer
[0147] B8: Adhesive layer / optical film
[0148] B9: Adhesive layer / optical film / hard coating
[0149] B10: Adhesive layer / optical film / anti-glare layer
[0150] B11: Adhesive layer / optical film / hard coating / anti-reflection layer
[0151] B12: Adhesive layer / optical film / anti-glare layer / anti-reflection layer
[0152] B13: Adhesive layer / optical film / hard coating / antifouling layer
[0153] B14: Adhesive layer / optical film / anti-glare layer / anti-fouling layer
[0154] B15: Adhesive layer / optical film / phase difference layer
[0155] [Surface panel for image display device]
[0156] The surface plate for an image display device of the present disclosure is a surface plate for an image display device in which a protective film is bonded to a resin plate or a glass plate, wherein the protective film includes the optical film of the present disclosure.
[0157] The protective film may be a film having a functional layer formed on the optical film. That is, the protective film may be the above-mentioned optical layered body.
[0158] As the resin plate or the glass plate, a resin plate or a glass plate commonly used as a surface plate of an image display device can be used.
[0159] In order to improve strength, the thickness of the resin plate or glass plate is preferably 10 μm or more. The upper limit of the thickness of the resin plate or glass plate is usually 5000 μm or less. In order to reduce thickness, the upper limit of the thickness of the resin plate or glass plate is preferably 1000 μm or less, more preferably 500 μm or less, and further preferably 100 μm or less.
[0160] [Image Display Panel]
[0161] The image display panel of the present disclosure has the above-mentioned optical film of the present disclosure on a display element.
[0162] The optical film may also be formed with a functional layer. That is, the image display panel of the present disclosure may have the above-mentioned optical layered body on the display element.
[0163] As display elements, there can be cited liquid crystal display elements, EL display elements such as organic EL display elements and inorganic EL display elements, plasma display elements, etc., and further LED display elements such as small LED display elements and micro LED display elements can be cited. These display elements can also have a touch panel function inside the display element.
[0164] As the display mode of the liquid crystal of the liquid crystal display element, IPS mode, VA mode, multi-domain mode, OCB mode, STN mode, TSTN mode, etc. can be cited. In the case where the display element is a liquid crystal display element, a backlight is required. As the backlight, a backlight using quantum dots and a backlight using white light emitting diodes can be cited.
[0165] The image display panel may be a foldable image display panel or a rollable image display panel. In addition, the image display panel may be an image display panel with a touch panel.
[0166] [Image display device]
[0167] The image display device of the present disclosure includes the image display panel of the present disclosure.
[0168] The image display device of the present disclosure preferably further includes a drive control unit electrically connected to the image display panel, and a housing that accommodates the image display panel, the drive control unit, and the like.
[0169] [Optical molded products]
[0170] The optical molded article of the present disclosure includes the optical resin of the present disclosure.
[0171] The optical molded article of the present disclosure may contain additives as components other than the optical resin of the present disclosure. Examples of the additives include ultraviolet absorbers, light stabilizers, antioxidants, and refractive index adjusters.
[0172] Since the optical molded article of the present disclosure has a resin component composed of the optical resin of the present disclosure, it is possible to suppress the occurrence of birefringence due to stress.
[0173] Examples of optical molded products include lenses, light guide plates, prism sheets, image display components, and light-transmitting covers. These optical molded products can be produced by general molding methods such as injection molding and extrusion molding.
[0174] Examples of the lens include AR lenses, VR lenses, MR lenses, convex lenses, concave lenses, meniscus lenses (meniscus lenses), diffraction lenses, Fresnel lenses, biconvex lenses, toroidal lenses, spherical lenses, and aspherical lenses. The lens disclosed herein is not limited to the types of the above lenses, and can be applied to general lenses.
[0175] It is preferable that an antireflection layer is provided on the surface of the lens.
[0176] The haze of the lens in accordance with JIS K7136:2000 is preferably 2.0% or less. The total light transmittance of the lens in accordance with JIS K7361-1:1997 is preferably 85% or more.
[0177] The light guide plate is a component mainly used for edge-light type surface light sources. The shape of the light guide plate can be, for example, a generally flat plate shape formed in such a way that at least one surface is used as a light incident surface and a surface substantially orthogonal thereto is used as a light exit surface. The light guide plate disclosed in the present invention is not limited to the light guide plates of the above-mentioned uses and shapes, and can be applied to general light guide plates.
[0178] A prism sheet is an optical component that changes the angle of light. A prism sheet is mainly used as a component for a surface light source. The shape of a prism sheet can be, for example, a roughly flat plate shape with a periodic structure on the surface of the light emitting side. Examples of the periodic structure include a pyramid shape, a structure array with a triangular cross section, and the like. The prism sheet disclosed in the present invention is not limited to the prism sheets of the above-mentioned uses and shapes, and can be applied to general prism sheets.
[0179] The image display component is a component for visually recognizing image light. Examples of the image display component include a transmissive screen, a vehicle-mounted panel, and a vehicle-mounted pillar.
[0180] The light-transmitting cover is used as a cover member for protecting a device that emits light, such as a LiDAR, or for protecting objects visible to humans, such as an instrument panel of a car.
[0181] The present disclosure includes the following [1] to
[13] .
[0182] [1] An optical resin, wherein 13 In the C-NMR spectrum, when the range of chemical shift from 141 ppm to 147 ppm is defined as the first range, and the range of chemical shift from 135 ppm to 141 ppm is defined as the second range, the ratio of the peak area of the peak in the first range to the peak area of the peak in the second range is less than 0.55.
[0183] [2] The optical resin according to [1], wherein the optical resin comprises an alternating copolymer of a maleimide-based monomer and a styrene-based monomer.
[0184] [3] The optical resin according to [2], wherein the maleimide-based monomer comprises at least one selected from maleimide and N-substituted maleimide substituted with a substituent having 1 to 6 carbon atoms.
[0185] [4] The optical resin according to [2], wherein the styrene-based monomer comprises at least one selected from the group consisting of styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene and p-methylstyrene.
[0186] [5] The optical resin according to [2], wherein at least one monomer selected from the maleimide monomer and the styrene monomer contains a biomass-derived component.
[0187] [6] The optical resin according to any one of [1] to [5], wherein the absolute value of the photoelastic coefficient of the optical resin is 6.0×10 -12 / Pa or less.
[0188] [7] The optical resin according to any one of [1] to [6], wherein the optical resin has a glass transition temperature of 100° C. to 190° C.
[0189] [8] An optical film comprising the optical resin according to any one of [1] to [7].
[0190] [9] The optical film according to [8], wherein the haze of the optical film according to JIS K7136:2000 is 2.0% or less.
[0191]
[10] A polarizing plate comprising: a polarizing element; a first transparent protective plate disposed on one side of the polarizing element; and a second transparent protective plate disposed on the other side of the polarizing element, wherein:
[0192] At least one of the first transparent protective plate and the second transparent protective plate includes the optical film described in [8] or [9].
[0193]
[11] A surface plate for an image display device, comprising a resin plate or a glass plate to which a protective film is laminated, wherein the protective film comprises the optical film according to [8] or [9].
[0194]
[12] An image display panel comprising the optical film according to [8] or [9] on a display element.
[0195]
[13] An image display device comprising the image display panel described in
[12] .
[0196]
[14] An optical molded article comprising the optical resin according to any one of [1] to [7].
[0197]
[15] The optical molded product according to
[14] , wherein the molded product is any one selected from a lens, a light guide plate, a prism sheet, an image display component, and a light-transmitting cover.
[0198] Example
[0199] The optical resin and the optical film of the present disclosure are specifically described below with reference to Examples and Comparative Examples. The optical resin and the optical film of the present disclosure are not limited to the embodiments described in the Examples.
[0200] 1. Evaluation and measurement
[0201] The optical resins and optical films obtained in the examples and comparative examples were subjected to the following measurements and evaluations. The measurements and evaluations were performed at locations free of defects such as foreign matter, damage, and wrinkles. The results are shown in Table 1. Unless otherwise specified, the following measurements and evaluations were performed in an atmosphere with a temperature of 23°C ± 5°C and a relative humidity of 40% to 65%. In addition, unless otherwise specified, the samples were exposed to the above atmosphere for 30 minutes to 60 minutes before each measurement.
[0202] 1-1. Based on 13 Calculation of peak area ratios in C-NMR spectrum measurement
[0203] The optical resins of the examples and comparative examples were measured. 13 C-NMR spectrum. The measuring device used was "AVANCE III HD" manufactured by Bruker Corporation, and the software used was "TopSpin3.2" manufactured by Bruker Corporation. The measuring conditions were as follows. The "cumulative number of times: 10,000 times" of the measuring condition means that the measuring result is the average value of 10,000 times of measurement. Based on the measuring results, the peak area ratio of the optical resin of the embodiment and the comparative example was calculated.
[0204] <Measurement Conditions>
[0205] Observed nucleus: 13C
[0206] Observation frequency: 100.65MHz
[0207] Measurement temperature: room temperature (23°C)
[0208] Determination solvent: DMSO-d6 (dimethyl sulfoxide, deuteration rate 99.9%)
[0209] Pulse program: zgig30 (quantitative determination method)
[0210] Pulse width: 10.0 μs
[0211] Waiting time: 15 seconds
[0212] Cumulative times: 10,000 times
[0213] Sample concentration (sample / measurement solvent): 100 mg / 1.0 ml
[0214] Sample solution volume: 0.75ml
[0215] Sample tube: NMR sample tube (manufactured by Wilmad, model: 535-PP-7)
[0216] <Calculation steps for peak area ratio>
[0217] After the measurement, the displayed spectrum is converted into an NMR spectrum, and the reference alignment is performed in a manner that the peak showing the maximum value near 39.5ppm becomes 39.52ppm among the 7 or so peaks (DMSO-d6 peaks) shown at 38.8ppm or more and 40.2ppm or less. The integral value of the peak shown at 141ppm or more and 147ppm or less (peak in the first range) and the peak shown at 135ppm or more and 141ppm or less (peak in the second range) is obtained, and the peak area ratio is calculated. The peak area ratio is expressed by the following formula.
[0218] Peak area ratio = (integrated value of the peak in the second range) / (integrated value of the peak in the first range)
[0219] On the software screen, click the "Pick Peaks" button and select the ppm range for which you want to calculate the integrated value. This will allow you to calculate the integrated value for each peak.
[0220] 1-2. Photoelastic coefficient
[0221] The samples were prepared from the optical films of the embodiments and comparative examples, and the photoelastic coefficient of the optical resin was measured using the prepared samples. The shape of the sample was as follows. The measuring device used was the trade name "Automatic Birefringence Control Device ABR-EX" of UNIOPT. The measuring conditions were as follows. The average value of the three measurements was used as the photoelastic coefficient of the embodiments and comparative examples.
[0222] <Measurement Conditions>
[0223] Deformation mode: tensile measurement
[0224] Measurement wavelength: 633nm
[0225] Measuring speed: 0.1mm / min
[0226] Tensile stress: 0~2N (apply stress at intervals of about 0.1N to measure delay)
[0227] Width of measuring part: 4~5mm
[0228] Calculation method: The photoelastic coefficient is calculated from the retardation in the tensile stress range of 0.3 to 2N, the width of the measurement section, and the film thickness.
[0229] <Shape of sample>
[0230] Figure 1 The shape of the sample. 1 , l 2 , l 3 , r, b 1 , b 2 , b 3 As described below. Figure 1 The "r" is the radius of curvature.
[0231] l 1 : 11.0mm
[0232] l 2 : 22.0mm
[0233] l 3 : 4.0mm
[0234] r: 3.0mm
[0235] b 1 : 16.0mm
[0236] b 2 : 4.5mm
[0237] b 3 : 2.0mm
[0238] 1-3. Refractive index
[0239] Samples were made from the optical films of the embodiments and comparative examples, and the refractive index of the optical resin at a wavelength of 589 nm was measured using the made samples. The shape of the sample was a quadrilateral of 10 mm × 10 mm. The measuring device used was a "prism coupler" produced by Metricon. During the measurement, the optical film was placed between the coupling head of the sample stand of the measuring device and the prism of the measuring device. During the measurement, an air phase was formed between the prism and the optical film. Measurements were performed at five wavelengths, namely, 404 nm, 594 nm, 656 nm, 786 nm, and 829 nm, and the refractive index at a wavelength of 589 nm was calculated using Cauchy's dispersion formula. The average value of the five measurements was taken as the refractive index of the embodiments and comparative examples.
[0240] 1-4. Total light transmittance, haze
[0241] The total light transmittance of the optical films of Examples and Comparative Examples according to JIS K7361-1:1997 and the haze of JIS K7136:2000 were measured using a haze meter (model: HM-150, Murakami Color Research Laboratory Co., Ltd.) 5 times, and the average of the three measurements excluding the maximum and minimum values was taken as the total light transmittance and haze of Examples and Comparative Examples.
[0242] 1-5. Light Leakage
[0243] Prepare a non-polarized light table (Sanwa Supply Co., Ltd. product number "400-TBL-006", front brightness: 1500 cd / m 2 ). On the above-mentioned light-transmitting table, two polarizing plates are arranged in such a way that their absorption axes are orthogonal to each other. The above-mentioned arrangement is the so-called "orthogonal Nicol" arrangement. Furthermore, an optical plate with a thickness of 1 mm made of the optical resin of the embodiment and the comparative example is arranged between the two polarizing plates, thereby preparing a sample for evaluation of light leakage. The size of the evaluation sample is 5 cm×5 cm.
[0244] In a dark room environment, when a load of 2N to 10N is applied to the optical plate of the above evaluation sample, observe whether light leakage occurs from various angles. 10 adults evaluate and grade according to the following criteria. The direction in which the load is applied to the optical plate is 45 degrees relative to the absorption axis of the polarizing plate.
[0245] Light leakage is determined by phase difference. Specifically, the greater the phase difference, the more it changes the polarization degree of light when orthogonal Nicol is applied. "Phase difference = film thickness × photoelastic coefficient × stress". Therefore, when the same film thickness and the same stress are applied, the greater the photoelastic coefficient, the greater the phase difference, and therefore the easier it is to cause light leakage.
[0246] A: More than 8 people answered that there was no light leakage.
[0247] B: The number of people who answered that there was no light leakage was more than 6 and less than 8
[0248] C: Less than 5 people answered that there was no light leakage
[0249] 1-6.Bending resistance
[0250] The mandrel test of the optical films of Examples and Comparative Examples was conducted in accordance with the cylindrical mandrel method of JIS K5600-5-1:1999, and was visually evaluated according to the following criteria. The test apparatus used was a JIS type 1 test apparatus. The test environment and sample drying conditions were in accordance with JIS regulations.
[0251] AA: No cracks occurred even when the mandrel diameter was 2 mm.
[0252] A: Cracks occurred when the mandrel diameter was 2 mm, but no cracks occurred when the mandrel diameter was 3 mm.
[0253] B: Cracks occurred when the mandrel diameter was 3 mm, but no cracks occurred when the mandrel diameter was 4 mm.
[0254] C: Cracks occurred when the mandrel diameter was 4 mm, but no cracks occurred when the mandrel diameter was 5 mm.
[0255] D: Cracks occurred when the mandrel diameter was 5 mm.
[0256] 1-7. Steel wool resistance
[0257] The optical films of the examples and comparative examples were subjected to a steel wool test to evaluate the steel wool resistance. Specifically, samples of 50 mm × 100 mm were cut out from the optical films of the examples and comparative examples. Cellotape (registered trademark) manufactured by Nichiban Co., Ltd. was used to fix the samples on a glass plate. 2 Steel wool (product name "Bonstar #0000", manufactured by Japan Steel Wool Co., Ltd.) was moved back and forth under a load of 1000 g to contact the sample surface. The moving speed of the steel wool was 50 mm / sec. After each reciprocating movement, the surface of the optical film was visually checked for damage and evaluated according to the following criteria.
[0258] A: There is no damage even after 5 reciprocating cycles.
[0259] B: There is no damage after one reciprocation, but there is damage after 2 to 5 reciprocations.
[0260] C: Even if it is reciprocated once, there will be damage
[0261] 1-8. Pencil hardness
[0262] The pencil hardness test of the optical films of Examples and Comparative Examples was carried out. The pencil hardness test was carried out under the following conditions (some conditions were changed from JIS) with reference to the scratch hardness (pencil method) of JIS K5600-5-4:1999.
[0263] <Conditions>
[0264] Speed: 1mm / s
[0265] Distance: 7mm
[0266] Temperature: 23℃±2℃
[0267] Relative humidity: 50±5%
[0268] Pencil angle: 45 degrees
[0269] · Test direction (direction of pencil scratching): The angle between the sample and the pencil is the acute angle. According to JIS regulations, the test is conducted in a direction of 135 degrees, which is an obtuse angle between the sample and the pencil. However, in this measurement, the test is conducted in a direction of 45 degrees, which is an acute angle.
[0270] Load: 500g
[0271] 1-9. Comprehensive evaluation of scratch resistance
[0272] The test results were "acceptable" when the steel wool resistance of 1-7 was B or higher and the pencil hardness of 1-8 was 3B or higher.
[0273] When the steel wool resistance of 1-7 was C or less and / or the pencil hardness of 1-8 was 4B or less, it was considered "unacceptable".
[0274] 1-10. Glass transition temperature
[0275] The glass transition temperatures of the optical resins of Examples and Comparative Examples were measured. The measuring apparatus used was "DSC-60" manufactured by Shimadzu Corporation. The measuring conditions were as follows.
[0276] <Measurement Conditions>
[0277] Sample volume: 10.0 mg
[0278] Sample container: Aluminum pan
[0279] Temperature conditions: Raise the temperature from room temperature to 220°C at 10°C / min. Maintain at 220°C for 3 minutes. Lower the temperature from 220°C to 20°C at -10°C / min. Maintain at 20°C for 3 minutes. Raise the temperature from 20°C to 220°C at 10°C / min. Maintain at 220°C for 3 minutes. Lower the temperature from 220°C to 20°C at -10°C / min.
[0280] Calculation of glass transition temperature: The midpoint of the transition temperature obtained by reading the DSC curve at the second heating was taken as the glass transition temperature. That is, the midpoint glass transition temperature of 9.3 (1) of JIS K7121:1987 was taken as the glass transition temperature of the optical resins of Examples and Comparative Examples.
[0281] 2. Production of optical resin and optical film
[0282] [Example 1]
[0283] A 500 ml removable flask was replaced with nitrogen. 37.5 g of cyclohexanone and 25.0 g of N-ethylmaleimide were placed in the removable flask and stirred with a stirring blade to prepare a solution. Furthermore, a solution in which 7.6 g of styrene and 0.03 g of a polymerization initiator (NOF Corporation, trade name: Perbutyl O) were dissolved in 3.8 g of cyclohexanone was placed in the removable flask. The removable flask was heated at 70°C for 8 hours in an oil bath. After cooling to room temperature, 367 g of methyl ethyl ketone was added to the removable flask, and then transferred to a 5 L flask. 2-isopropanol was slowly added to the flask to obtain a visibly turbid solution. 1 kg of 2-isopropanol was added to the visibly turbid solution at one time to obtain a white slurry. The white slurry was filtered. The operation of washing the filtered slurry with 2-isopropanol and filtering was repeated 5 times to obtain a powder. The recovered powder was dried under reduced pressure at 110° C. for 6 hours, thereby obtaining a polymer 1 (optical resin of Example 1).
[0284] 1.0 g of polymer 1 was dissolved in 8.0 g of methyl ethyl ketone to obtain a coating liquid. The coating liquid was applied to a polyethylene terephthalate film (Cosmoshine A4160, manufactured by Toyobo) by a casting method using an applicator. After being placed in an oven at 100°C for 5 minutes, it was placed in an oven at 130°C for 3 minutes and taken out to obtain a coating film formed by drying the coating liquid. The coating film was peeled off from the polyethylene terephthalate film to obtain an optical film (film thickness 20 μm) of Example 1.
[0285] [Example 2]
[0286] Polymer 2 (optical resin of Example 2) was obtained in the same manner as in Example 1 except that the amount of N-ethylmaleimide was changed from 25.0 g to 2.5 g, the amount of styrene was changed from 7.6 g to 8.3 g, and the amount of the polymerization initiator was changed from 0.03 g to 0.01 g.
[0287] 1.0 g of polymer 2 was dissolved in 6.0 g of methyl ethyl ketone to obtain a coating liquid. The coating liquid was applied to a polyethylene terephthalate film (Cosmoshine A4160, manufactured by Toyobo) by a casting method using an applicator. After being placed in an oven at 100° C. for 5 minutes, it was placed in an oven at 130° C. for 3 minutes and taken out to obtain a coating film formed by drying the coating liquid. The coating film was peeled off from the polyethylene terephthalate film to obtain an optical film (film thickness 39 μm) of Example 2.
[0288] [Comparative Example 1]
[0289] A 500 ml removable flask was replaced with nitrogen. 21.0 g of cyclohexanone and 1.0 g of maleimide were placed in the removable flask and stirred with a stirring blade to prepare a solution. Furthermore, a solution in which 9.7 g of styrene and 0.02 g of a polymerization initiator (NOF Corporation, trade name: Perbutyl O) were dissolved in 6.0 g of cyclohexanone was placed in the removable flask. The removable flask was heated at 70°C for 8 hours in an oil bath. After cooling to room temperature, 200 g of tetrahydrofuran was added to the removable flask, and then transferred to a 5 L flask. 2-isopropanol was slowly added to the flask to obtain a visibly turbid solution. 1 kg of 2-isopropanol was added to the visibly turbid solution at one time to obtain a white slurry. The white slurry was filtered. The operation of washing the filtered slurry with 2-isopropanol and filtering was repeated 5 times to obtain a powder. The recovered powder was dried under reduced pressure at 110° C. for 6 hours, thereby obtaining a polymer 3 (optical resin of Comparative Example 1).
[0290] 1.0 g of polymer 3 was dissolved in 4.0 g of tetrahydrofuran to obtain a coating liquid. The coating liquid was applied to a polyethylene terephthalate film (Cosmoshine A4160, manufactured by Toyobo) by a casting method using an applicator. After being placed in an oven at 70°C for 5 minutes, it was placed in an oven at 130°C for 5 minutes and taken out to obtain a coating film formed by drying the coating liquid. The coating film was peeled off from the polyethylene terephthalate film to obtain an optical film (film thickness 40 μm) of Comparative Example 1.
[0291] [Example 3]
[0292] A 500 ml removable flask was purged with nitrogen. 250.0 g of toluene and 20.0 g of biomass-derived maleic anhydride were placed in the removable flask and stirred with a stirring blade to prepare a solution. Furthermore, 21.2 g of styrene and 0.20 g of a polymerization initiator (azobisisobutyronitrile) were placed in the removable flask.
[0293] The above-mentioned removable flask was heated at 60°C for 2 hours in an oil bath to obtain a slurry of polymer precipitation. After the above-mentioned slurry was cooled to room temperature, 150 g of toluene was added to the above-mentioned removable flask, and the above-mentioned slurry was further filtered. The operation of washing the filtered slurry with toluene and filtering was repeated 5 times to obtain a powder. The recovered powder was dried under reduced pressure at 110°C for 6 hours, thereby obtaining a polymer 4'.
[0294] A 500 ml detachable flask was replaced with nitrogen. 50.0 g of N-methylpyrrolidine and 5.0 g of polymer 4' were placed in the above detachable flask, and stirred with a stirring blade to prepare a solution. 7.2 g of butylamine was added dropwise to the above detachable flask over 45 minutes. The oil bath was set to 180°C and heated for 2 hours, then cooled to room temperature, and then 300 g of methyl ethyl ketone was added and stirred to prepare a solution. After the above solution was transferred to a 5L flask, 2-isopropanol was slowly added to obtain a visibly turbid solution. 1 kg of 2-isopropanol was added to the visibly turbid solution at one time to obtain a white slurry. The above slurry was filtered. The operation of washing the filtered slurry with 2-isopropanol and filtering was repeated 5 times to obtain a powder. The recovered powder was dried under reduced pressure at 110°C for 6 hours to obtain polymer 4 (optical resin of Example 3).
[0295] 1.0 g of polymer 4 was dissolved in 8.0 g of methyl ethyl ketone to obtain a coating liquid. The coating liquid was applied to a polyethylene terephthalate film (Cosmoshine A4160, manufactured by Toyobo) by a casting method using an applicator. After being placed in an oven at 100° C. for 5 minutes, it was placed in an oven at 130° C. for 3 minutes and taken out to obtain a coating film formed by drying the coating liquid. The coating film was peeled off from the polyethylene terephthalate film to obtain an optical film (film thickness 33 μm) of Example 3.
[0296] [Example 4]
[0297] Polymer 5 (optical resin of Example 4) and an optical film of Example 4 were obtained in the same manner as in Example 3 except that 20.0 g of biomass-derived maleic anhydride was changed to 20.0 g of non-biomass-derived maleic anhydride.
[0298] [Comparative Example 2]
[0299] A 500 ml removable flask is replaced with nitrogen. A solution containing 250.0 g of toluene, 40.0 g of styrene and 0.20 g of a polymerization initiator (azobisisobutyronitrile) is placed in the removable flask. The removable flask is heated at 60°C for 8 hours in an oil bath to obtain a slurry in which a polymer is precipitated. After the slurry is cooled to room temperature, 150 g of toluene is added to the removable flask, and the slurry is further filtered. The operation of washing and filtering the filtered slurry with toluene is repeated 5 times to obtain a powder. The recovered powder is dried under reduced pressure at 110°C for 6 hours to obtain polymer 6 (optical resin of Comparative Example 6).
[0300] 1.0 g of polymer 6 was dissolved in 5.0 g of methyl ethyl ketone to obtain a coating liquid. The coating liquid was applied to a polyethylene terephthalate film (Cosmoshine A4160, manufactured by Toyobo) by a casting method using an applicator. After being placed in an oven at 100° C. for 5 minutes, it was placed in an oven at 130° C. for 3 minutes and taken out to obtain a coating film formed by drying the coating liquid. The coating film was peeled off from the polyethylene terephthalate film to obtain an optical film (film thickness 20 μm) of Comparative Example 2.
[0301] [Example 5]
[0302] Polymer 7 (optical resin of Example 5) was obtained in the same manner as in Example 1 except that the amount of N-ethylmaleimide was changed from 25.0 g to 1.5 g, the amount of styrene was changed from 7.6 g to 7.5 g, and the amount of the polymerization initiator was changed from 0.03 g to 0.02 g.
[0303] Next, an optical film of Example 5 was obtained in the same manner as in Example 2 except that the polymer 2 was changed to the polymer 7.
[0304] [Comparative Example 3]
[0305] Polymer 8 (optical resin of Comparative Example 3) was obtained in the same manner as in Example 1 except that the amount of N-ethylmaleimide was changed from 25.0 g to 1.0 g, the amount of styrene was changed from 7.6 g to 7.5 g, and the amount of the polymerization initiator was changed from 0.03 g to 0.02 g.
[0306] Next, an optical film of Comparative Example 3 was obtained in the same manner as in Example 2 except that the polymer 2 was changed to the polymer 8.
[0307] [Example 6]
[0308] Polymer 9 (optical resin of Example 6) was obtained in the same manner as in Example 1 except that 25.0 g of N-ethylmaleimide was changed to 10.0 g of N-methylmaleimide, the amount of styrene was changed from 7.6 g to 9.4 g, and the amount of the polymerization initiator was changed from 0.03 g to 0.3 g.
[0309] Next, an optical film of Example 6 was obtained in the same manner as in Example 2 except that the polymer 2 was changed to the polymer 9.
[0310] [Example 7]
[0311] A 500 ml separable flask was purged with nitrogen. 250.0 g of toluene and 20.0 g of maleic anhydride were placed in the separable flask and stirred with a stirring blade to prepare a solution. Furthermore, 21.2 g of styrene and 0.20 g of a polymerization initiator (azobisisobutyronitrile) were placed in the separable flask.
[0312] The removable flask was heated at 60°C for 2 hours in an oil bath to obtain a slurry of polymer precipitation. After the slurry was cooled to room temperature, 150 g of toluene was added to the removable flask, and the slurry was further filtered. The filtered slurry was washed with toluene and filtered for 5 times to obtain a powder. The recovered powder was dried under reduced pressure at 110°C for 6 hours to obtain a polymer 10'.
[0313] A 500 ml removable flask was replaced with nitrogen. 40.0 g of N-methylpyrrolidine and 10.0 g of polymer 10' were placed in the removable flask, and stirred with a stirring blade to form a solution. 5.9 g of propylamine was added dropwise to the removable flask over 45 minutes. The oil bath was set to 80°C and heated for 1 hour, and then set to 200°C and heated for 1 hour, and then cooled to room temperature, and then 100 g of methyl ethyl ketone was added and stirred to form a solution. After the above solution was transferred to a 5L flask, 2-isopropanol was slowly added to obtain a visibly turbid solution. 1 kg of 2-isopropanol was added to the visibly turbid solution at one time to obtain a white slurry. The above slurry was filtered. The operation of washing the filtered slurry with 2-isopropanol and filtering was repeated 5 times to obtain a powder. The recovered powder was dried under reduced pressure at 110°C for 6 hours to obtain polymer 10 (optical resin of Example 7).
[0314] 3.0 g of polymer 10 was dissolved in 13.0 g of 1,3-dioxolane to obtain a coating liquid. The coating liquid was applied to a polyethylene terephthalate film (Cosmoshine A4160, manufactured by Toyobo) by a casting method using an applicator. After being placed in an oven at 100° C. for 5 minutes, it was placed in an oven at 130° C. for 3 minutes and taken out to obtain a coating film formed by drying the coating liquid. The coating film was peeled off from the polyethylene terephthalate film to obtain an optical film (film thickness 37 μm) of Example 7.
[0315] [Example 8]
[0316] A polymer 11 (optical resin of Example 8) was obtained in the same manner as in Example 7 except that propylamine was changed to isopropylamine.
[0317] Next, an optical film of Example 8 was obtained in the same manner as in Example 7 except that the polymer 10 was changed to the polymer 11.
[0318] [Example 9]
[0319] A polymer 12 (optical resin of Example 9) was obtained in the same manner as in Example 7 except that 5.9 g of propylamine was changed to 7.2 g of isobutylamine.
[0320] Next, an optical film of Example 9 was obtained in the same manner as in Example 7 except that the polymer 10 was changed to the polymer 12.
[0321] [Example 10]
[0322] A polymer 13 (optical resin of Example 10) was obtained in the same manner as in Example 7 except that 5.9 g of propylamine was changed to 8.6 g of isoamylamine.
[0323] Next, an optical film of Example 10 was obtained in the same manner as in Example 7 except that the polymer 10 was changed to the polymer 13.
[0324] [Comparative Example 4]
[0325] Into a 2L autoclave (material: SUS316, manufactured by Nitto High Pressure), add 472g of isopropyl acetate, 100g of maleic anhydride and 0.14g of polymerization initiator (Perbutyl O), seal and inject nitrogen. Pressurize 57g of isobutylene into the autoclave and stir. Heat the autoclave to 70°C for 10h to obtain a slurry in which the polymer is precipitated. After cooling the slurry to room temperature, add 500ml of isopropyl acetate to the autoclave and further filter the slurry. Repeat the operation of washing and filtering the filtered slurry with isopropyl acetate 5 times to obtain a powder. The recovered powder is dried under reduced pressure at 110°C for 20h to obtain polymer 14'.
[0326] A 500 ml removable flask was replaced with nitrogen. 40.0 g of N-methylpyrrolidine and 10.0 g of polymer 14' were placed in the removable flask, and stirred with a stirring blade to form a solution. 7.7 g of propylamine was added dropwise to the removable flask over 45 minutes. The oil bath was set to 80°C and heated for 1 hour, and then set to 200°C and heated for 1 hour, and then cooled to room temperature, and then 100 g of methyl ethyl ketone was added and stirred to form a solution. After the above solution was transferred to a 5 L flask, 2-isopropanol was slowly added to obtain a visibly turbid solution. 1 kg of 2-isopropanol was added to the visibly turbid solution at one time to obtain a white slurry. The above slurry was filtered. The operation of washing the filtered slurry with 2-isopropanol and filtering was repeated 5 times to obtain a powder. The recovered powder was dried under reduced pressure at 110°C for 6 hours to obtain polymer 14 (optical resin of Comparative Example 4).
[0327] 3.0 g of polymer 14 was dissolved in 15.0 g of 1,3-dioxolane to obtain a coating liquid. The coating liquid was applied to a polyethylene terephthalate film (Cosmoshine A4160, manufactured by Toyobo) by a casting method using an applicator. After being placed in an oven at 100° C. for 5 minutes, it was placed in an oven at 130° C. for 3 minutes and taken out to obtain a coating film formed by drying the coating liquid. The coating film was peeled off from the polyethylene terephthalate film to obtain an optical film (film thickness 34 μm) of Comparative Example 4.
[0328] [Comparative Example 5]
[0329] A polymer 15 (optical resin of Comparative Example 5) was obtained in the same manner as in Comparative Example 4 except that 7.7 g of propylamine was changed to 9.5 g of isobutylamine.
[0330] Next, an optical film of Comparative Example 5 was obtained in the same manner as in Comparative Example 4 except that the polymer 14 was changed to the polymer 15.
[0331] [Comparative Example 6]
[0332] 10.0 g of N-methylmaleimide and 0.01 g of Perbutyl O as a polymerization initiator were added to a sealed glass tube. After nitrogen substitution, the oil bath was set to 70°C and heated for 24 hours. After heating, the mixture was cooled to room temperature, and 100 g of methyl ethyl ketone was added and stirred to prepare a solution. After the above solution was transferred to a 5 L flask, 2-isopropanol was slowly added to obtain a visibly turbid solution. 1 kg of 2-isopropanol was added to the visibly turbid solution at one time to obtain a white slurry. The above slurry was filtered. The operation of washing the filtered slurry with 2-isopropanol and filtering was repeated 5 times to obtain a powder. The recovered powder was dried under reduced pressure at 110°C for 6 hours to obtain polymer 16 (optical resin of Comparative Example 6).
[0333] Next, an optical film of Comparative Example 6 was obtained in the same manner as in Comparative Example 4 except that the polymer 14 was changed to the polymer 16.
[0334] [Comparative Example 7]
[0335] A polymer 17 (optical resin of Comparative Example 7) was obtained in the same manner as in Comparative Example 6 except that N-methylmaleimide was changed to N-ethylmaleimide.
[0336] Next, an optical film of Comparative Example 7 was obtained in the same manner as in Comparative Example 4 except that the polymer 14 was changed to the polymer 17.
[0337] [Comparative Example 8]
[0338] A polymer 18 (optical resin of Comparative Example 8) was obtained in the same manner as in Comparative Example 6 except that N-methylmaleimide was changed to N-propylmaleimide.
[0339] Next, an optical film of Comparative Example 8 was obtained in the same manner as in Comparative Example 4 except that the polymer 14 was changed to the polymer 18.
[0340] [Table 1]
[0341]
[0342] [Table 2]
[0343]
[0344] The results of Tables 1 and 2 confirm that the optical resin and optical film of the examples can suppress birefringence due to stress, and thus can suppress light leakage. In addition, by comparing Example 3 using maleic anhydride from biomass with Example 4 using maleic anhydride from non-biomass, it can be confirmed that the optical resin and optical film of the present disclosure can suppress birefringence due to stress even if using materials from biomass, and thus can suppress light leakage.
[0345] In addition, from the results of Tables 1 and 2, it can be confirmed that the optical resins and optical films of Examples can improve the scratch resistance.
[0346] In addition, from the results of Tables 1 and 2, it can be confirmed that the optical films of Examples 2 to 10 having lowered glass transition temperatures can improve bending resistance.
Claims
1. An optical resin, wherein: Regarding the optical resin 13 In the C-NMR spectrum, when the range of chemical shift from 141 ppm to 147 ppm is defined as the first range, and the range of chemical shift from 135 ppm to 141 ppm is defined as the second range, the ratio of the peak area of the peak in the first range to the peak area of the peak in the second range is less than 0.
55.
2. The optical resin according to claim 1, wherein The optical resin comprises an alternating copolymer of maleimide monomers and styrene monomers.
3. The optical resin according to claim 2, wherein: The maleimide monomer includes one or more selected from maleimide and N-substituted maleimide substituted with a substituent having 1 to 6 carbon atoms.
4. The optical resin according to claim 2, wherein: The styrene-based monomer includes one or more selected from the group consisting of styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, and p-methylstyrene.
5. The optical resin according to claim 2, wherein: At least one monomer selected from the maleimide monomer and the styrene monomer contains a biomass-derived component.
6. The optical resin according to claim 1 or 2, wherein: The absolute value of the photoelastic coefficient of the optical resin is 6.0×10 -12 / Pa or less.
7. The optical resin according to claim 1 or 2, wherein: The optical resin has a glass transition temperature of 100° C. to 190° C. An optical film comprising the optical resin according to claim 1 or 2.
9. The optical film according to claim 8, wherein: The optical film has a haze of 2.0% or less in accordance with JIS K7136:2000.
10. A polarizing plate comprising: a polarizing element; a first transparent protective plate disposed on one side of the polarizing element; and a second transparent protective plate disposed on the other side of the polarizing element, wherein: At least one of the first transparent protective plate and the second transparent protective plate includes the optical film of claim 8 .
11. A surface plate for an image display device, which is a surface plate for an image display device in which a protective film is attached to a resin plate or a glass plate, wherein: The protective film comprises the optical film according to claim 8 . 12 . An image display panel comprising the optical film according to claim 8 on a display element. 13 . An image display device comprising the image display panel according to claim 12 .
14. An optical molded article comprising the optical resin according to claim 1 or 2.
15. The optical molded article according to claim 14, wherein The molded product is any one selected from a lens, a light guide plate, a prism sheet, an image display component, and a light-transmitting cover.
Citation Information
Patent Citations
Optical polymer material, optical film, display device, optical polymer material manufacturing method, and optical film manufacturing method
JP2020126229A